Iron Speciation and Physiological Analysis Indicate that Synechococcus sp. PCC 7002 Reduces Amorphous and Crystalline Iron Forms in Synthetic Seawater Medium - Annie Vera Hunnestad; Anne Ilse Maria Vogel; Maria Guadalupe Digernes; Murat Van Ardelan; Martin Frank Hohmann-Marriott (Journal of Marine Science and Engineering, 2020)
Cyanobacteria have high iron requirements due to iron-rich photosynthetic machineries. Despite the high concentrations of iron in the Earth’s crust, iron is limiting in many marine environments due to iron’s low solubility. Oxic conditions leave a large portion of the ocean’s iron pool unavailable for biotic uptake, and so the physiochemical properties of iron are hugely important for iron’s bioavailability. Our study is the first to investigate the effect of iron source on iron internalization and extracellular reduction by Synechococcus sp. PCC 7002. The results indicated that the amorphous iron hydrolysis species produced by FeCl3 better support growth in Synechococcus through more efficient iron internalization and a larger degree of extracellular reduction of iron than the crystalline FeO(OH). An analysis of dissolved iron (II) indicated that biogenic reduction took place in cultures of Synechococcus grown on both FeCl3 and FeO(OH).